Recent Advances in Thermally Activated Delayed Fluorescent Polymer—Molecular Designing Strategies - Yin, Xia; He, Ying; Wang, Xu; Wu, Zexin; Pang, Erbao; Xu, Jing; Wang, Jun-an (Frontiers in Chemistry, 2020)
Thermally activated delayed fluorescent (TADF) materials, as the third generation of organic electroluminescent materials, have many advantages over other organic light-emitting diodes (OLEDs) materials, such as 100% internal quantum efficiency, no doping of heavy metals, and avoiding the shortages of ordinary fluorescent materials and phosphorescent materials. So it is considered to be the most competitive organic light-emitting materials, and has great application prospects in the field of OLEDs. So far, small-molecule TADF materials have achieved high quantum yield and full-color range of red, green, and blue. However, TADF polymers suitable for low-cost and easily scalable solution processing are less developed, which are confined by the preparation methods and polymers designing, and there are still challenges of increasing quantum efficiency and strengthening device performance. This review mainly summarizes different synthesis strategies of TADF polymers and the latest development in the field. Special attention is focused on illustrating the designing and structure-property relationship of TADF polymers, and finally, an outlook is given for the design and application prospect of TADF polymers in the future.